An Unusual Case of Streptococcus anginosus Group Pyomyositis Diagnosed Using Direct 16S Ribosomal DNA Sequencing - Andrew Walkty; John M Embil; Kim Nichol; James Karlowsky (Canadian Journal of Infectious Diseases and Medical Microbiology)
Bacteria belonging to the Streptococcus anginosus group (Streptococcus intermedius, Streptococcus constellatus and Streptococcus anginosus) are capable of causing serious pyogenic infections, with a tendency for abscess formation. The present article reports a case of S anginosus group pyomyositis in a 47-year-old man. The pathogen was recovered from one of two blood cultures obtained from the patient, but speciation was initially not performed because the organism was considered to be a contaminant (viridans streptococci group). The diagnosis was ultimately confirmed using 16S ribosomal DNA sequencing of purulent fluid obtained from a muscle abscess aspirate. The present case serves to emphasize that finding even a single positive blood culture of an organism belonging to the S anginosus group should prompt careful evaluation of the patient for a pyogenic focus of infection. It also highlights the potential utility of 16S ribosomal DNA amplification and sequencing in direct pathogen detection from aspirated fluid in cases of pyomyositis in which antimicrobial therapy was initiated before specimen collection.